A randomized, open‐label, phase 2, multicenter trial of gemcitabine with pazopanib or gemcitabine with docetaxel in patients with advanced soft‐tissue sarcoma - Somaiah, Neeta; Van Tine, Brian Andrew; Wahlquist, Amy E.; Milhem, Mohammed M.; Hill, Elizabeth G.; Garrett‐Mayer, Elizabeth; Armeson, Kent E.; Schuetze, Scott M.; Meyer, Christian F.; Reuben, Daniel Y.; Elias, Anthony D.; Read, William L.; et al. (Cancer, 2021)
Background Therapeutic options for patients with advanced soft‐tissue sarcoma (STS) are limited. The goal of the current phase 2 study was to examine the clinical activity and safety of the combination of gemcitabine plus pazopanib, a multityrosine kinase inhibitor with activity in STS. Methods The current randomized, phase 2 trial enrolled patients with advanced nonadipocytic STS who had received prior anthracycline‐based therapy. Patients were assigned 1:1 to receive gemcitabine at a dose of 1000 mg/m2 on days 1 and 8 with pazopanib at a dose of 800 mg daily (G+P) or gemcitabine at a dose of 900 mg/m2 on days 1 and 8 and docetaxel at a dose of 100 mg/m2 on day 8 (G+T) every 3 weeks. Crossover was allowed at the time of disease progression. The study used a noncomparative statistical design based on the precision of 95% confidence intervals for reporting the primary endpoints of median progression‐free survival (PFS) and rate of grade ≥3 adverse events (AEs) for these 2 regimens based on the intent‐to‐treat patient population (AEs were graded using version 4.0 of the National Cancer Institute Common Terminology Criteria for Adverse Events). Results A total of 90 patients were enrolled: 45 patients on each treatment arm. The median PFS was 4.1 months for each arm (P = .3, log‐rank test). The best overall response of stable disease or better (complete response + partial response + stable disease) was the same for both treatment arms (64% for both the G+T and G+P arms). The rate of related grade ≥3 AEs was 82% for the G+T arm and 78% for the G+P arm. Related grade ≥3 AEs occurring in ≥10% of patients in the G+T and G+P arms were anemia (36% and 20%, respectively), fatigue (29% and 13%, respectively), thrombocytopenia (53% and 49%, respectively), neutropenia (20% and 49%, respectively), lymphopenia (13% and 11%, respectively), and hypertension (2% and 20%, respectively). Conclusions The data from the current study have demonstrated the safety and efficacy of G+P as an alternative to G+T for patients with nonadipocytic STS. The results of the current trial suggest similar efficacy and tolerability when comparing the gemcitabine and pazopanib (G+P) regimen with the gemcitabine and docetaxel (G+T) regimen. In patients who are not suitable for treatment with G+T, the G+P regimen is a reasonable alternate for the second‐line treatment of patients with metastatic nonadipocytic sarcomas.